Green transition for vulnerable households? Insights from behavioral science on what works (and what doesn't) - Moleskis, Melina; Solomou, Pantelis; Ikinci, Meltem; Zachariadis, Theodoros (Frontiers in Sustainable Energy Policy, 2025)
Energy poverty remains a pressing issue across Europe, particularly as the EU prepares to launch the Social Climate Fund in 2026. This paper serves as a review, drawing on behavioral science literature and existing evidence to provide actionable insights and practical guidance for policy-makers on designing and implementing grant schemes that effectively reach households vulnerable to energy poverty. Specifically, we identify cognitive and structural barriers—often overlooked in conventional policy approaches—that prevent vulnerable households from accessing or fully utilizing available financial support. While our recommendations are broadly applicable across the EU, we focus on the case of Cyprus, where energy poverty is high, and previous initiatives have faced significant challenges. By integrating behavioral insights into policy design, we aim to illustrate how grant schemes financed through the Social Climate Fund launching in 2026 can be made more accessible and effective for decision-makers of vulnerable households, ultimately paving the way for a more equitable and green transition.